Transaortic TAVI Is a Valid Alternative to Transapical Approach. Issue 5 (10th March 2015) - O' Sullivan, Katie E.; Hurley, Eoghan T.; Segurado, Ricardo; Sugrue, Declan; Hurley, John P.
ABSTRACT Background and Aim Transcatheter aortic valve implantation (TAVI) can be performed via a number of different anatomical approaches based on patient characteristics and operator choice. The aim of this study was to compare procedural outcomes between transaortic (TAo) and transapical (TA) approaches in an effort to establish whether any differences exist. Methods A systematic review and meta‐analysis of the current literature reporting outcomes for patients undergoing TAo and TA TAVI was performed to compare outcomes using each vascular approach to valve deployment. Results A total of 10 studies and 1736 patients were included. A total of 193 patients underwent TAo and 1543 TA TAVI. No significant difference in 30‐day mortality was identified (TAo 9.4, TA 10.4 p = 0.7). There were no significant differences identified between TAo and TA TAVI in procedural success rate (96.3% vs. 93.7% p = 0.3), stroke and transient ischemic attack (TIA) incidence (1.8% vs. 2.3% p = 0.7), major bleed (5.8% vs. 5.5% p = 0.97) or pacemaker insertion rates (6.1% vs. 7.4% p = 0.56). In addition, the incidence of clinically significant paravalvular regurgitation (PVR) was the same between groups (6.7% vs. 11% p = 0.43). Conclusion Comparison of TAo and TA approaches revealed equivalent outcomes in 30‐day mortality, procedural success, major bleeding, stroke/TIA incidence, pacemaker insertion rates and paravalvular leak. Heart teams should be familiar with the use of both TA and TAo access and tailor their selection on a case‐to‐case basis. doi: 10.1111/jocs.12527 (J Card Surg 2015;30:381–390)